“We have our reasons”: Exploring the acceptability of pre-exposure prophylaxis among gay, bisexual, and other men who have sex with men in Ghana - Gloria Aidoo-Frimpong; Gamji Rabiu Abu-Ba’are; Amos Apreku; Richard Panix Amoh-Otu; Edem Zigah; Prince Amu-Adu; Samuel Amuah; Laura Nyblade; Kwasi Torpey; LaRon E. Nelson (BMC Public Health)
Abstract Background Ghanaian men who have sex with men (MSM) face significant HIV disparities compared to the general population in Ghana. Pre-exposure prophylaxis (PrEP) is a highly effective tool for HIV prevention. Previous studies on the perspectives of PrEP use among Ghanaian MSM identified high interest in PrEP among this population. However, the knowledge from the previous research, which was the best available evidence at the time, was primarily hypothetical because those data were collected before any real-world implementation of PrEP in Ghana. The analysis aims to identify and understand the factors currently influencing PrEP acceptance. Methods We analyzed focus group (n = 8) data with Ghanaian MSM. We transcribed, coded, identified, and analyzed the responses using descriptive thematic analysis. Results We identified two broad themes. Under theme one, which indicated almost universal awareness of PrEP but inaccuracies about PrEP were common, these were the categories: (1) Awareness of PrEP and antiretroviral therapy [ART], (2) confusion between pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis, (3) event-driven perceptions of PrEP usage, (4) Mixed understanding of PrEP: distinguishing PrEP from ART, and (5) advocacy for a comprehensive educational approach. Theme two revealed that PrEP acceptability was influenced by a mix of individual and intrapersonal factors such as (1) hesitancy towards PrEP uptake due to perceived limited benefit, (2) extending HIV, sex, and same-gender sexual relations stigma to PrEP affects uptake, (3) perceived lack of information, concerns about side effects, and cost. Conclusions To bridge the gap between awareness, knowledge, and acceptability, HIV prevention programs should address access barriers and incorporate community-derived strategies.